Fluor-silane modified nano-calcium carbonate (CaCO3) as a hydrophobic coating for the conservation of sandstone via bio-inspired design - Ye Wang; Wenxin Xiao; Danqian Wang; Jingfeng Wang (Biogeotechnics)
Ancient cultural relics built of red sandstone have high historical value. However, due to the acceleration of the industrialization process of human civilization, increasingly frequent acid rain has caused irreversible damage to the surface of red sandstone artifacts. In this research, a fluor-silane modified nano-calcium carbonate (CaCO3) was prepared as a biomimetic hydrophobic coating for the conservation of red sandstone inspired by the lotus leaf effect. Characterizations and immersion tests were carried out to assess the protective properties of the coating. XRD, FT-IR, TEM and SEM were combined to characterize the morphology of the coating. In addition, the water contact angle was measured before and after immersion in the simulated acid rain. The results indicate that this kind of hydrophobic nano-CaCO3 coating effectively protected the sandstone from the deleterious effects of acid rain.